PENGARUH DISIPLIN KERJA DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PT. VAN AROMA - Sanggita; Andi Heru Susanto (Melati Institute, 2023)
Background: PT Van Aroma is one of the largest essential oil suppliers in Indonesia and continues to grow. The problem in PT Van Aroma is the decline in employee performance due to lack of work discipline, lack of a sense of responsibility for the job, and employees arriving not on time (late) and unstable attendance rates due to the covid 19 pandemic. This study aims to analyze the effect of work discipline and job satisfaction on the performance of PT Van Aroma employees. Methodology: This study used an associative quantitative approach with a total sample of 89 employees. The instrument used is a questionnaire. Instrument quality testing includes validity tests and reliability tests. Data analysis uses descriptive analysis, while hypothesis testing uses multiple linear regression analysis. Results: The results showed that work discipline has a significant of 0.00 smaller than ? 0.05, it can be concluded that work discipline (X1) partially has a positive and significant effect on performance (Y) at PT Van Aroma. Job satisfaction has a significant of 0.03 smaller than ? 0.05, it can be concluded that job satisfaction (X2) partially has a positive and significant effect on performance (Y) at PT. Van Aroma. Based on the results of the F test simultaneously between the independent variables on the dependent variable, a significant level of 0.000 <0.05 is obtained, meaning that work discipline and job satisfaction have a significant effect on employee performance at PT. Van Aroma. Research limitations: Data analysis is carried out on a limited sample and does not consider other variables that affect employee performance.